Kawin Kontrak Menurut Agama Islam, Hukum Dan Realita Dalam Masyarakat - Sri Hariati (Fakultas Hukum Universitas Mataram, 2015)
Marriage is something that has become human nature, which aims to establish mahligai marriage a happy home and eternal well-being and spiritual birth according to which dreamed dreams. But the reality in the community is abusing the marriage are some women who do the marriage contract. Contract marriage is a marriage that is based on an agreement to live together as husband and wife in a certain time period, accompanied by exchange for one of the parties. The desire to gain economic advantage and meet the biological needs, is the purpose of the execution of contracts. The implementation process of the marriage contract is processed with the provisions of Islamic religious law with the help of a chaplain with the reason the process easier and faster. Although marriage processed according to Islamic law, but in building the household does not animate Islamic law because it is based on a contract / agreement that it is contrary to Islamic law itself.